2023
DOI: 10.1177/03635465221140923
|View full text |Cite
|
Sign up to set email alerts
|

Acute Adductor Muscle Injury: A Systematic Review on Diagnostic Imaging, Treatment, and Prevention

Abstract: Background: Controversies remain regarding the diagnosis, imaging, and treatment of acute adductor injuries in athletes. Purpose: To investigate the diagnostic imaging, treatment, and prevention of acute adductor injuries based on the most recent and relevant scientific evidence. Study Design: Systematic review; Level of evidence, 4. Methods: The PubMed and Web of Science databases were searched according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines to identify articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Second, we considered that the conservative treatment usually provides early RTP at the same pre-injury level with no additional risk of recurrence. Comparative studies have shown that athletes undergoing a conservative approach experience a faster recovery compared to those undergoing surgical re-attachment (3-12 vs. 10-16 weeks), 8,12,15 although the surgical group was composed of patients with more severe injuries. However, in our case, the player resumed sport activity after 16 weeks (a longer time compared to other cases where conservative strategies were used), as we waited that all RTP criteria were fully satisfied (subjective and objective measures).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we considered that the conservative treatment usually provides early RTP at the same pre-injury level with no additional risk of recurrence. Comparative studies have shown that athletes undergoing a conservative approach experience a faster recovery compared to those undergoing surgical re-attachment (3-12 vs. 10-16 weeks), 8,12,15 although the surgical group was composed of patients with more severe injuries. However, in our case, the player resumed sport activity after 16 weeks (a longer time compared to other cases where conservative strategies were used), as we waited that all RTP criteria were fully satisfied (subjective and objective measures).…”
Section: Discussionmentioning
confidence: 99%
“…5,7 Adductor injuries are usually observed at the proximal musculotendinous junction, but tendinous ruptures at the origin on the pubic bone, known as avulsions, are uncommon. 8 These injuries can occur in isolation or with associated lesions of the pyramidal and/or pectineus muscles or anterior pubic ligament, forming the so-called pyramidalisanterior pubic ligament-AL complex (PLAC). 9 In football (also called soccer in the United States), these lesions are commonly observed (about 23% of the muscle injuries) in middleaged athletes (22-30 years old) who engage in activities that require strenuous and vigorous movements, particularly in a position of wide hip adduction with extension and internal rotation (kicking, shooting, sprinting, and change of direction).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We corroborate existing literature demonstrating that surgical reattachment for proximal adductor avulsion injuries leads to restoration of preinjury levels of function. n Alex Chang, BS 1 Mark Zoland, MD 1 Srino Bharam, MD, MBA 1 1 Lenox Hill Hospital, New York, New York Email address for S. Bharam: srino.bharam@gmail.com…”
Section: Discussionmentioning
confidence: 99%
“…Athletic groin injuries are commonly encountered in sports that involve abrupt changes in speed and direction 1-3 . Proximal adductor avulsion injuries are a relatively uncommon and severe subset of groin injury that occurs when the adductor longus muscle tendon completely separates from its origin at the pubis.…”
mentioning
confidence: 99%